The potential of genomic epidemiology: capitalizing on its practical use for impact in the healthcare setting - Pacchiarini, Nicole; McKerr, Caoimhe; Morgan, Mari; Connor, Thomas R.; Williams, Christopher (Frontiers in Public Health, 2025)
The rapid detection and containment of healthcare-associated infections (HCAIs) is critical in preventing and controlling infectious disease outbreaks within healthcare settings. Whole genome sequencing (WGS) has emerged as a powerful tool for tracking the transmission dynamics of pathogens and when used alongside traditional epidemiological methods it can better inform our understanding of the pathogen origin, pathway and extent of transmission. Additionally, WGS can aid in identifying previously unrecognized reservoirs of infection, allowing for more effective control strategies and targeted interventions. This article describes the incorporation of WGS into infectious disease management in Wales and explores it in the context of COVID-19 and Clostridioides difficile. We also describe the developments made to the workforce in Wales to enable the expansion of WGS and reflect on the resources, infrastructure and training frameworks still required.